Pengaruh Kapitalisme pada Kelompok Sosialita: Menelaah Hedonistic Consumerism di Kalangan Hermes Lovers - Devita Prinanda (Lembaga penelitian dan pengabdian kepada Masyarakat, 2018)
Consumerism is a development of consumption terms. Consumption is fundamental to meeting people's needs while consumerism is an act of excessive consumption. People who consume desires from needs are called hedonistic consumerism. This phenomenon is an economic habit, especially among the elite. A thick hedonistic culture will be a negative impression because it relates to something that is excessive. The capitalism system underlies people's behavior to become consumers who are hedonistic.Branded bags are a product of capitalism. The existence of this product is favored by certain circles because the price reaches hundreds of millions. This bag collector is spread all over the world and the great collectors have a dependency on these luxury bags and consume them continuously. However, this hedonism activity does not only have a negative impact. From a hobby of collecting luxury bags can be used as a profitable investment and even across national borders. Furthermore, the writer will also explain alternative assumptions for a socialistic lifestyle that is hedonistic.